2018
DOI: 10.1530/rep-17-0457
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen is an important mediator of mast cell activation in ovarian endometriomas

Abstract: Endometriosis is an estrogen-dependent disease. Previous research has shown that abnormal enzymes associated with estrogen (E2) metabolism and an increased number of mast cells (MCs) in endometriomas are implicated in the pathogenesis of endometriosis. However, it remains unclear how MCs mediate the role of E2 in endometriosis. Accordingly, we investigated whether E2 was associated with the number of MCs, and the rate of degranulation, in local ovarian endometriomas, as well as the role of E2 on MCs during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…Increasing evidence supports that activated and degranulating mast cells play an important role in the development of pain, hyperalgesia and dysmenorrhea [37,38]. Our previous study also demonstrate that the activity and degranulation of mast cells play an important role in endometriosis-related dysmenorrhea [14]. Moreover, it is reported that mast cells contribute to the development of inflammation in adenomyosis [10].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Increasing evidence supports that activated and degranulating mast cells play an important role in the development of pain, hyperalgesia and dysmenorrhea [37,38]. Our previous study also demonstrate that the activity and degranulation of mast cells play an important role in endometriosis-related dysmenorrhea [14]. Moreover, it is reported that mast cells contribute to the development of inflammation in adenomyosis [10].…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, increasing evidence supports that the activated mast cell is regarded as a director of common inflammatory pathways contributing to chronic neuropathic pain and may play a role in pathogenesis of adenomyosis [11][12][13]. Our previous study also showed that the recruitment and degranulation of mast cells play an important role in endometriosis-related dysmenorrhea [14]. In addition, recent research found adenomyosis-induced pain resembles neuropathic pain [15].…”
Section: Ivyspringmentioning
confidence: 67%
See 1 more Smart Citation
“…Positive correlations between ER and MCs suggest that estrogen is a chemotactic molecule for MCs. We were especially interested in the correlation between MCit and ER + carcinoma cells, as some studies have proved that estrogen activates mast cells in ovarian endometriosis and that human uterine mast cells express ERβ (19,20). Others have shown that administration of estrogens leads to eosinophilic and MCs infiltrations (21).…”
Section: Cells (Mcs) In Breast Carcinomas Stained For Anti-tryptase (mentioning
confidence: 99%
“…Endometriosis-associated inflammation is able to stimulate and sensitize peripheral nerves. Researchers found that activation of (DRG) mast cells by estrogen can trigger the release of NGF and also sensitize dorsal root ganglion cells [ 9 ]. This neuroimmune interaction mediated by estrogen is correlated with the severity of endometriosis-associated dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%